An amphiphilic organosilicon framework (AOF): a new solid Pickering catalyst carrier. Issue 5 (9th April 2019) - Yu, Honghao; Zou, Houbing; Dai, Jinyu; Shi, Zhiqiang; Wang, Runwei; Zhang, Zongtao; Qiu, Shilun
Abstract : The amphiphilicity of the AOF carrier originates from the amphiphilic pyridine groups in the frameworks of the nanoparticles. Abstract : Amphiphilic solid nanoparticles can stabilize a biphasic system to form a Pickering emulsion like organic amphiphilic surfactants, and have profound implications for oil-aqueous biphasic reactions. In the current work, for the first time, we prepared an amphiphilic organosilicon framework (AOF) simply by hydrolysis and condensation of the amphiphilic organosiloxane precursor 2, 5-bis[( E )-2-(triethoxysilyl)vinyl]pyridine [BTOSVP] which can be used as a Pickering emulsifier and a catalyst carrier for a W–O emulsion in various systems. After catalyst TS-1 was implanted in the amphiphilic AOF carrier, it turned into a solid Pickering catalyst, yolk–shell TS-1@AOF, that can stabilize water–oil emulsions and catalyze reactions at the liquid/liquid interface. The obtained Pickering catalyst showed remarkable activity toward the epoxidation reaction of 1-hexene in water with hydrogen peroxide (H2 O2 ) as oxidant.